We've to Build the Pipeline. What's the Problem? What's Next? The Remix. Issue 3 (September 2018) - Sharpe, Rhonda Vonshay
Despite a history of initiatives to strengthen the doctorate pipeline and mentoring programs for graduate students and junior faculty, the economics profession has failed to achieve a representative level of diversity across ethnicity, gender and race. This National Economic Association presidential address looks at the 20-year production, 1996-2015, of economists by ethnicity, gender, race, and residential status with an interest in the production of Black economists. The findings suggest there is cause for alarm as the number of undergraduate economics degrees conferred to Black women was stagnant, and there has been a decrease in the number of doctorates conferred to Blacks men. In addition, the number of undergraduate mathematics degrees conferred to Blacks has decreased, which may have dire consequences for the economics and mathematics doctorate pipeline. Recommendations that promote the professional lives of Black and minority economists are provided.